Approaching the Distinction between Intuition and Insight - Zhang, Zhonglu; Lei, Yi; Li, Hong (Frontiers in Psychology, 2016)
Intuition and insight share similar cognitive and neural basis. Though, there are still some essential differences between the two. Here in this short review, we discriminated between intuition and insight in two aspects. First, intuition and insight are towards different aspects of information processing. Whereas intuition involves judgment about “yes or no”, insight is related to “what” is the solution. Second, tacit knowledge play different roles in between intuition and insight. On the one hand, tacit knowledge is conducive to intuitive judgment. On the other hand, tacit knowledge may first impede but later facilitate insight occurrence. Furthermore, we share theoretical and methodological views on how to access the distinction between intuition and insight.